PENERAPAN GOOD CORPORATE GOVERNANCE TERHADAP PENCEGAHAN FRAUD: SEBUAH LITERATUR REVIEW - Marciano, Benny; Syam, Ardiansyah; Ahmar, Nurmala; Gayatri, Maria; Suyanto, Suyanto (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2018)
Fraud is any action taken illegally for personal gain. Good Corporate Governanceis a set of rules related to the company's control process implementation whichinvolving all stakeholders to ensure the company's performance in achieving theorganization's vision and mission. This study aims to determine the effect of theimplementation of Good Corporate Governance on fraud prevention efforts. This study was conducted through a literature review of 15 published articles. Literaturesearches were carried out on various electronic databases such as Google Scholar,Scopus, ProQuest, ScienceDirect, ACM Digital Library, IEEE Xplore, and Springerby entering keywords, namely